PENGATURAN KEWENANGAN DESA DALAM PENGELOLAAN PARIWISATA - I Wayan Eka Darma Putra; Anak Agung Ketut Sukranatha (Kertha Negara : Journal Ilmu Hukum, 2014)
This paper titled Setting village in Tourism Management Authority. Problemsoccurred that Act No. 32 year 2004 on Regional Government does not clearly informvillage authorities in the field of tourism. This paper aims to understand and knowabout setting authority in the management of village tourism. This paper, usingnormative legal research with descriptive method. The conclusion is Act No. 32 year2004 on Regional Government of village authorities have not specified in terms oftourism management. The provisions concerning the authority of the village intourism management can be seen in the Minister of Home Affairs Number 30 Year2006 on Procedures for Delivery of Government Affairs District / City To Ruralaffairs explained that one of the district / city that can be handed over to the village isthe field of tourism, covering : (a) Management of tourist attraction in the villageoutside of the tourism master plan, (b) Management of recreation and publicentertainment places in the village, (c) establishment licenses Recommendationcottage in the village in the tourist area, and (d) Assist the hotel and restaurant taxcollection in the village.